Analysis of financial performance in small rural farms: Fish farming - Petersen, Marcelo Guilhermino [UNESP]; Queiroz, Timóteo Ramos [UNESP]; Santos, David Ferreira Lopes [UNESP]; Casagrande, Élton Eustáquio [UNESP]; Dos Reis Lucente, Adriano [UNESP] (Centro Universitario de Maringa, 2019)
Current study proposes and evaluates a financial management model for small rural fish farming companies to provide information for decision taking within this type of agribusiness, and compares its performance with other activities on the market. Featuring 5.5 million hectares of fresh water, Brazil has 0.76% of aquaculture production worldwide. The informality of such activity and decision taking are peculiar to Brazil, restricting a better and greater exploitation of the country's potential resources. Empirical studies have focused on economic evaluations of specific projects. However, the income of such fish farming companies in Brazil is a challenge and still unknown. The case was analyzed during six months with visits on the spot, participating observations and analysis of documents. The fish farm lies in the state of Mato Grosso do Sul and produces Nile tilapias (Oreochromis niloticus) in net tanks, with a nominal capacity of 1930 tons/year. Results range from methodological structuring to identification, acknowledgement and expenditure through production plots till the consolidation within a structure of cash flow and property control. The above information allows budget administration, cash and performance by indexes for fish farming.
Proposta de análise de desempenho financeiro em pequenas empresas rurais: O caso da piscicultura
Keywords: Agribusiness; Aquiculture; Financial performance; Net tanks; Oreochromis niloticus